2021
DOI: 10.1016/j.cophys.2020.09.016
|View full text |Cite
|
Sign up to set email alerts
|

The role of inflammation in hypertension: novel concepts

Abstract: Hypertension remains the most important modifiable risk factor for the development of cardiovascular disease. While it is clear that inflammation plays a pivotal role in the development and maintenance of hypertension, several novel discoveries have been made within the past decade that have advanced the field and have provided new mechanistic insights. First, recent studies have identified a central role of sodium-induced immune cell activation in the pathogenesis of hypertension by altering the gut microbiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 69 publications
(97 reference statements)
2
51
0
2
Order By: Relevance
“…Inflammation is a complex process involving multiple cell types and secreted factors, many of which have been linked to hypertension. 59 61 The importance of the immune system in the pathophysiology of hypertension may relate primarily to its effects on inflammation, which is involved not only in BP regulation and thus in the development of hypertension, but also in the initiation and progression of cardiovascular and renal tissue damage/remodeling. 60 , 62 There is now extensive experimental and also clinical evidence that hypertension is associated with inflammation and immune cell activation, processes that are driven in large part by oxidative stress.…”
Section: Impact Of Dysregulated Immunoinflammation In Hypertension Onmentioning
confidence: 99%
See 3 more Smart Citations
“…Inflammation is a complex process involving multiple cell types and secreted factors, many of which have been linked to hypertension. 59 61 The importance of the immune system in the pathophysiology of hypertension may relate primarily to its effects on inflammation, which is involved not only in BP regulation and thus in the development of hypertension, but also in the initiation and progression of cardiovascular and renal tissue damage/remodeling. 60 , 62 There is now extensive experimental and also clinical evidence that hypertension is associated with inflammation and immune cell activation, processes that are driven in large part by oxidative stress.…”
Section: Impact Of Dysregulated Immunoinflammation In Hypertension Onmentioning
confidence: 99%
“… 60 , 62 , 64 The resulting molecular events induce protein oxidation and dysregulated cell signaling, leading to inflammation, cell migration, and immune cell activation, among many other effects. 59 61 …”
Section: Impact Of Dysregulated Immunoinflammation In Hypertension Onmentioning
confidence: 99%
See 2 more Smart Citations
“…It is estimated that 92.1 million US adults have at least one of the US population 6 . Previous studies have found that inflammation is an underlying cause of hypertension and that IsoLGs play a role 7 . Hypertensive stimuli, including angiotensin II, catecholamines, aldosterone, and excess dietary salt, induce IsoLG accumulation in antigen presenting cells including dendritic cells (DCs), which in turn activate T cells to proliferate and produce inflammatory cytokines that contribute to hypertension 8 , 9 .…”
Section: Introductionmentioning
confidence: 98%